Antimicrobial and anticancer activities of Allium hirtifolium boiss hydromethanolic extract - Ismail, Salmiah (2011)
The emergence of multiple resistances exhibited by pathogenic microorganisms against commercial antimicrobial drugs, the undesirable side effects of certain antibiotics as well as the limited number of anticancer agents have led scientists to search for new antimicrobial substances from various sources such as medicinal plants. In fact, the usage of herbs or medicinal plants is still practiced until this modern time since these herbs are said to provide safe and effective treatments against many diseases. In line with discovery of plant-based drugs, the present study focused on studying medicinal properties of Allium hirtifolium known as Persian Shallot. This edible plant belongs to Allium genus, which has been used in folk medicine in many parts of Iran and Mediterranean region and it is believed to play an important role in the healthcare aspect. In this current study, the effectiveness of hydromethanolic Allium hirtifolium Boiss bulbs was studied against six different pathogenic bacteria including Staphylococcus aureus, Methicillin Resistant Staphylococcus aureus (MRSA), Methicillin Sensitive Staphylococcus aureus (MSSA), Salmonella typhimurium, Escherichia coli O157:H7 and Escherichia coli, one fungus (Candida albicans), three different types of viruses Herpes Simplex Virus Type 1 (HSV-1), Herpes Simplex Virus Type 2 (HSV-2) and Respiratory Syncytial Virus (RSV), one type of normal human fibroblast cell line (MRC-5) and four different types of cancer cell lines consist of human breast cancer cells (MCF-7), human cervical cancer cells (HeLa), human liver cancer cells (HepG-2) and human colon cancer cells (HT-29) by in vitro system. The result of disk diffusion assay showed that the extract at different concentrations (120, 60, 30, 15 mg/ml) was effective against all Grams positive bacteria as the zone of inhibition ranged from 14.25- 8.50 mm. Whereas, for Gram negative bacteria (E. coli and E. coli O157:H7), only higher concentrations (120, 60 and 30 mg/ml) were effective with the inhibition zones ranged from 12.50- 8.00 mm. The highest activity of the extract against Salmonella typhimurium was achieved only at the highest concentration (120 mg/ml). The significant result was obtained for the fungus Candida albicans with the zone of inhibition ranging from 24-17 mm compared to commercial antifungal drug (Amphotericin B) which was 14 mm in diameter. To confirm the antibacterial and antifungal properties of the extract, the Minimal Inhibitory Concentration (MIC) and the Minimal Bactericidal/Fungicidal Concentration (MBC/MFC) were determined by Broth Dilution Assay. The starting concentration for this assay was 120 mg/ml and two fold serial dilutions were prepared from this concentration until the last concentration which was 0.94 mg/ml. The MIC for all the tested pathogenic bacteria and fungus were ranged from 120.00- 3.75 mg/ml while MBC values were ranged from 120.00- 7.50 mg/ml indicating that shallot extract was effective. Moreover, morphological study using Scanning Electron Microscopy revealed that shallot extract altered the morphology of Candida albicans in comparison with Amphotericin B. The MTT (3-(4,5-Dimethylthiazol-2-Yl)-2,5-Diphenyltetrazolium Bromide) Assay was performed in order to determine the cytotoxicity of the extract on normal human cell line (MRC-5) as well as against cancer cells. This extract is shown to be less cytotoxic to the human normal fibroblast cells whereby 60% of the cells were viable at the concentration of 1 mg/ml even though at different time of incubations (24, 48 and 72 hours). A positive result was only obtained for MCF-7 and HeLa cancer cells with the IC50 value 0.28 mg/ml and 0.11 mg/ml, respectively. At the concentration of 0.25 mg/ml, the anticancer property exhibited by the extract on MCF-7 and HeLa cancer cells was confirmed by Dual Assay whereby the induction of apoptosis through the activation of caspase-3 was observed at this concentration. In addition, cell cycle analysis showed that the treated cancer cells accumulated in the sub-G1 phase which is a hallmark of apoptotic cell death. In terms of antiviral activity, the positive results were shown for HSV-1 and RSV through intracellular assay whereby the Selective Index values were 7.11 and 5.16, respectively. These findings suggest that the hydromethanolic extract of Persian Shallot might be useful in treatment of diseases caused by these viruses. In general, the hydromethanolic extract of Allium hirtifolium Boiss has a strong potential to be used as an antibacterial, antifungal, antiviral as well as anticancer agents.